2023
DOI: 10.1186/s12913-023-10291-3
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of unprofessional behaviour between staff in acute care hospitals: a realist review

Justin Avery Aunger,
Jill Maben,
Ruth Abrams
et al.

Abstract: Background Unprofessional behaviours (UB) between healthcare staff are rife in global healthcare systems, negatively impacting staff wellbeing, patient safety and care quality. Drivers of UBs include organisational, situational, team, and leadership issues which interact in complex ways. An improved understanding of these factors and their interactions would enable future interventions to better target these drivers of UB. Methods A realist review … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…However, the relationship between these and unprofessional behaviour has rarely been examined. How unprofessional behaviour can be an antecedent to increased risks to patient safety were exemplified in the accounts provided by staff, particularly how such behaviour can undermine psychological safety [24] . Analyses of the reports also identified a number of situational factors and organizational characteristics beyond individual factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the relationship between these and unprofessional behaviour has rarely been examined. How unprofessional behaviour can be an antecedent to increased risks to patient safety were exemplified in the accounts provided by staff, particularly how such behaviour can undermine psychological safety [24] . Analyses of the reports also identified a number of situational factors and organizational characteristics beyond individual factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…personality) that may increase the propensity to engage in unprofessional behaviour, including high workload, time pressures, inadequate coordination, teamwork, supervision and leadership, and organizational constraints (e.g. lack of equipment or resources) [ 24 , 25 ]. These potentially error-producing factors should be targets of organization-wide improvement strategies, along with focussing on efforts to change individual behaviour [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training senior staff as messengers and providing them with the skills to address unprofessional behaviour, as well as rewarding staff for positive behaviour are all strategies which are incorporated into the Ethos program, but there will be local variation in the extent to which these strategies are effective and sustained. As a recent realist review [ 9 ] has identified, the problem of unprofessional behaviour needs to be tackled in a holistic way recognising a multitude of factors in different contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Unprofessional behaviour in healthcare is widespread [ 1 3 ] and significantly undermines the effective functioning of teams, staff wellbeing, patient experience and safety, and negatively impacts organisational productivity and costs [ 3 8 ]. Unprofessional behaviour encompasses a spectrum, from overtly hostile, bullying and inappropriate behaviours such as physical and verbal abuse, to more subtle behaviours such as passive aggression, rudeness and incivility [ 3 , 9 ]. Consistently high rates of incivility and bullying between healthcare co-workers have been demonstrated in surveys from multiple countries and settings [ 2 , 10 12 ].…”
Section: Introductionmentioning
confidence: 99%